Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

in mirror formula prove m=f/f-u.

in mirror formula prove 


m=f/f-u.

Grade:

3 Answers

Shyama P
35 Points
9 years ago

1/f= 1/u+1/v

multiplying with u =>

u/f= 1+u/v

m=-v/u Sub in eqn

u/f-1=-1/m

Solve & u get the ans:

Sanandanan M
38 Points
9 years ago

(1/v) + (1/u) = (1/f)

(1/v) = (1/f) - (1/u) = ((u-f)/f)

multiply throughout by -u and take reciprocal

-(v/u) = (f/(f-u))

that is magnification.

Prashant Sinha
26 Points
one month ago
Mirror Formula- 1/v+1/u=1/f
1/v=(1/f)-(1/u)
1/v=(u-f)/fu
v=fu/(u-f) ---------- (1)
Magnification (m) = -(v)/u
m=-(fu/(u-f))/u           (From (1))
u-f can be written as -(f-u)
so it will become
m=(fu/f-u)/u
m=f/(f-u)        (By cancelling u)
Hence proved.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free